2013
DOI: 10.1016/j.yfrne.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and activational effects of sex steroids on kisspeptin neuron development

Abstract: Kisspeptin, encoded by the Kiss1 gene, is a neuropeptide required for puberty and adult reproductive function. Understanding the regulation and development of the kisspeptin system provides valuable knowledge about the physiology of puberty and adult fertility, and may provide insights into human pubertal or reproductive disorders. Recent studies, particularly in rodent models, have assessed how kisspeptin neurons develop and how hormonal and non-hormonal factors regulate this developmental process. Exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 153 publications
6
36
0
Order By: Relevance
“…These cells are additional candidates for relaying estrogen signals to the GnRH neuronal network and might be responsible for developmental compensation and rescue of fertility in female mice lacking kisspeptin neurons (30). Although neurotransmitter expression and steroid hormone sensitivity remained static in ARC kisspeptin neurons throughout the female reproductive development, the number of catecholaminergic and estrogen-sensitive AVPV kisspeptin neurons increased during puberty, consistent with previous results (17,18). We show that both catecholaminergic and noncatecholaminergic AVPV kisspeptin neurons communicate with GnRH neurons.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These cells are additional candidates for relaying estrogen signals to the GnRH neuronal network and might be responsible for developmental compensation and rescue of fertility in female mice lacking kisspeptin neurons (30). Although neurotransmitter expression and steroid hormone sensitivity remained static in ARC kisspeptin neurons throughout the female reproductive development, the number of catecholaminergic and estrogen-sensitive AVPV kisspeptin neurons increased during puberty, consistent with previous results (17,18). We show that both catecholaminergic and noncatecholaminergic AVPV kisspeptin neurons communicate with GnRH neurons.…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, kisspeptin neurons are commonly referred to as AVPV or ARC kisspeptin neurons, not taking into consideration potential heterogeneity within these populations. Consistent with the idea of kisspeptin neuron subpopulations within the AVPV and ARC, previous studies have shown that individual kisspeptin neurons differ in neurotransmitter content and steroid hormone receptor expression (13)(14)(15)(16)(17)(18). Furthermore, electrophysiological characterization of genetically labeled kisspeptin neurons in female mice has revealed differences between individual kisspeptin neurons within a nucleus as well as in between the two nuclei (19 -21).…”
mentioning
confidence: 53%
“…The neonatal testosterone surge in male rodents induces irreversible sexual differentiation in the brain to delete the surge module 185 . This situation correlates well with the permanent suppressive effects of perinatal testosterone upon the RP3V kisspeptin neuron population in male rodents 186,187 . By contrast, gonadectomized adult male monkeys can exhibit an LH surge in response to the appropriate gonadal steroid regimen and an unidentified testicular factor is thought to persistently suppress the surge in adult nongonadectomized males 188,189 .…”
Section: Pubertal Development Of the Gnrh Surgesupporting
confidence: 70%
“…Recent rodent studies have underlined the role of perinatal sex steroids in programming the sexual differentiation of Kisspeptin expression in the AVPV (reviewed in Poling and Kauffman (2013)). At later developmental stages, such as puberty, AVPV Kisspeptin neurons may also be further regulated by E2 to exhibit a typical female pattern.…”
Section: Critical Windows For the Effects Of Sex Steroids On Pubertymentioning
confidence: 99%